2023
DOI: 10.3390/jcm12020423
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Bile Duct Tumor Thrombus: A Case Report and Literature Review of 890 Patients Affected by Uncommon Primary Liver Tumor Presentation

Abstract: Bile duct tumor thrombus (BDTT) is an uncommon finding in hepatocellular carcinoma (HCC), potentially mimicking cholangiocarcinoma (CCA). Recent studies have suggested that HCC with BDTT could represent a prognostic factor. We report the case of a 47-year-old male patient admitted to the University Hospital of Bari with abdominal pain. Blood tests revealed the presence of an untreated hepatitis B virus infection (HBV), with normal liver function and without jaundice. Abdominal ultrasonography revealed a cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Despite the remarkable progress in diagnostic imaging, it is often difficult to differentiate hepatocellular carcinoma with intraductal growth of the bile duct, especially in cases with obstructive jaundice as the initial symptom and no obvious intrahepatic mass, from hilar bile duct carcinoma or intraductal growth of the bile duct-type hepatoma [ 10 ]. Correct preoperative diagnosis has been reported in only 26.5% of cases, indicating the challenges of clinical diagnosis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the remarkable progress in diagnostic imaging, it is often difficult to differentiate hepatocellular carcinoma with intraductal growth of the bile duct, especially in cases with obstructive jaundice as the initial symptom and no obvious intrahepatic mass, from hilar bile duct carcinoma or intraductal growth of the bile duct-type hepatoma [ 10 ]. Correct preoperative diagnosis has been reported in only 26.5% of cases, indicating the challenges of clinical diagnosis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, it has been widely demonstrated that minimally invasive liver surgery achieves intraoperative and postoperative results comparable to those obtained by open surgery both in terms of complications and overall survival [27,[67][68][69][70][71][72][73][74][75][76], especially when R0 resection is performed. This has also been reported by randomized clinical trials [77,78].…”
Section: Colorectal Cancer and Liver Metastasesmentioning
confidence: 97%
“…In this clinical scenario, AI is also applied to patients affected by colorectal cancer (CRC) [21,25]. CRC is one of the main cancers worldwide, and about 40-50% of patients will develop colorectal liver metastases (CRLM) either during oncological follow-up, after primary tumor resection, or during postoperative chemotherapy regimen administration [1,9,26,27]. Therefore, more than 20% of CRC patients have distant metastases at the time of diagnosis [28], registering a 5-year OS of about 15% compared to 80-90% in patients with local disease.…”
Section: Introductionmentioning
confidence: 99%
“…About 25–30% of patients diagnosed with colorectal cancer develop liver metastases (CRLM) during the disease making it the most frequent secondary liver tumor [ 1 , 2 , 3 , 4 ]. The incidence of synchronous liver metastasis ranges from 13.8% to 17.1% in epidemiology, while the incidence for metachronous CRLM is reported between 7.6% and 15.1% [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%